IMPLEMENTATION OF DALY BMS AND MODULXHM604 AS A BATTERY PACK FOR ECGO2 ELECTRIC MOTORCYCLES TO IMPROVE SAFETY, CAPACITY AND FAST CHARGING - Amin, Muhammad; Ricki Ananda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
Abstrack: This research aims to improve battery performance and safety on the ECGO2 electric motorcycle by re-assembling the battery system using 18650 lithium cells, Daly BMS 13S/7A battery management system, and XH-M604 module. The configuration used is 13S5P (65 cells), resulting in a total voltage of 48.1 V and a capacity of 14 Ah, or equivalent to 673.4 Wh of energy. Compared to the ECGO2 built-in battery that requires 4-7 hours of charging time, this system is able to speed up charging to ±1.6 hours using a 7 A current charger. Test results using an oscilloscope show that the voltage of the assembled battery is more stable under load than that of a single battery, with minimal ripple. The estimated operating time of an 800 W electric motor using a 673.4 Wh battery is about 50 minutes. To achieve 2 hours of operation, the 13S10P configuration or energy-saving mode (400-500 W) can be used. The system is also more cost-effective at Rp2,678 per Wh compared to the manufacturer's version of Rp4,464 per Wh, as well as improved safety against leakage and overheating. Keywords: 18650 lithium battery; daly bms; electric motorcycle; fast charging. Abstrak: Penelitian ini bertujuan untuk meningkatkan performa dan keamanan baterai pada sepeda motor listrik ECGO2 dengan merakit ulang sistem baterai menggunakan sel lithium 18650, sistem manajemen baterai Daly BMS 13S/7A, dan modul XH-M604. Konfigurasi yang digunakan adalah 13S5P (65 sel), menghasilkan tegangan total 48,1 V dan kapasitas 14 Ah, atau setara dengan energi 673,4 Wh. Dibandingkan baterai bawaan ECGO2 yang memerlukan waktu pengisian 4–7 jam, sistem ini mampu mempercepat pengisian menjadi ±1,6 jam menggunakan charger arus 7 A. Hasil pengujian menggunakan osiloskop menunjukkan bahwa tegangan baterai rakitan lebih stabil di bawah beban dibandingkan baterai tunggal, dengan ripple minimal. Estimasi lama pengoperasian motor listrik 800 W menggunakan baterai 673,4 Wh adalah sekitar 50 menit. Untuk mencapai 2 jam pengoperasian, dapat digunakan konfigurasi 13S10P atau mode hemat energi (400–500 W). Sistem ini juga lebih hemat biaya dengan efisiensi harga Rp2.678 per Wh dibandingkan Rp4.464 per Wh versi pabrikan, serta meningkatkan keamanan terhadap kebocoran dan panas berlebih. Kata kunci: baterai lithium 18650; daly bms; sepeda motor listrik; pengisian daya cepat.